Fetal medicine at present - Huamán Guerrero, Moisés (2016)
In recent decades there has been a special interest in studying the fetus, which has originated important progress in research for different medical specialties, based mainly on the development of fetal ultrasound application in diagnosis of fetal complications. In addition, there has been progress in technology for fetal genetic study from material directly obtained from the fetus or from maternal circulation, and interventions that improve pre- and post-natal prognosis. This progress encompasses a new multidisciplinary medical specialty that considers the fetus as an individual patient in the context of the mother-fetus relationship, establishing prophylactic treatments, medical therapies directly applied to the fetus or through the mother, interventions guided by ultrasonography, (limited) open surgery and fetoscopy, with reasonable advantages compared to conventional treatments. This reality compels to revise ethical and legal aspects related to the not-yet born, and implementation of modifications in health care offer and pre- and post-graduate curricula.